Race, science, and medicine, 1700-1960 - Harris, Bernard, 1961-; Ernst, Waltraud, 1955- (Routledge, 1999)
Race, Science and Medicine, 1700-1960 brings together current critical research into the role played by racial ideas in the production of medical knowledge, throwing new light on three centuries of racial and medical history.
Keywords: Social medicine -- History.; Colonization -- Health aspects -- History.; Imperialism -- Health aspects -- History.; Science -- Social aspects -- History.; Medicine -- History.; Social Medicine -- history; Social Sciences -- history; Racial Groups -- history; History of Medicine; Médecine sociale -- Histoire.; Colonisation -- Aspect sanitaire -- Histoire.; Impérialisme -- Aspect sanitaire -- Histoire.; Sciences -- Aspect social -- Histoire.; Médecine -- Histoire.; history of medicine.; MEDICAL -- History.; Colonization -- Health aspects; Imperialism -- Health aspects; Science -- Social aspects; Social medicine; Geneeskunde.; Rassendiscriminatie.; Kolonialisme.; Wetenschap.; History